Assessment of Health Workers Performanceat primary Schools in Missan Governorate / Iraq - Khalida A.S. Abdul-Jabbar, Assistant Professor *, Haider Ebbrah.Nasser, B.CS *** *Assistant Professor, Dr. Khalida A.S. Abdul-Jabbar ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
Objectives:To assess of health workers performance at primary schools in Missan governorate through health center activities and by local school observation. Methods:A descriptive cross-sectional study conducted at 16(50%) primary health care centers and primary schools 64 (10%)who where randomly selected (Multi-stage sample) in Missan governorate. Ministry of health (M.O.H ) school health workers performance assessment checklist was designed for observation the performance of school health staff in delivering primary health care services to schools within the geographical area of each center was used for data collection.Results:The results showed that, there were deficiencies in some school health workers activities. The percentage of health centers that had the epidemiological surveillance for diseases in schoolswere present in40.6%, whilein 29.6% of primary health centers environmental examinationwere implemented. The measurement (height, weight, body mass index)and Preventive dose of vitamin (A) in all of health centres were not implemented 100%.In 15.6% of health centers implemented examination of students dental and coordination between immunization unit and school health unit was present partially in100 % of health centres. The examined visual acuity for studentswere observed in 57.8%.Recommendation:Adequate coordination between health centers and schools administrations, An organized co-operation between health, educational and environmental authorities to maintain the environment of school at the standard levels, Increase number of medical training courses and widening the sharing area to involve all staff members and the inclusion of school health staff in  training courses inside and outside the country and increase the workforce in primary health care centers. Provision of physicians, dentist and sight checker in each of the school health unit.